PROSES PENYELESAIAN SANKSI POLISI PENJAGA TAHANAN TERHADAP TAHANAN YANG MELARIKAN DIRI DI KEPOLISIAN RESOR KOTA PEKANBARU - Donni Saputra; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Police Institution is a state institution that aims to create order, peaceand security in the community both in terms of prevention, eradication, andprosecution of criminal acts. One of the police authorities is detention. Detaineesare guarded by custody officers, if the detainee escapes causing a legal problem,in the implementation of the possibility of abuse of authority by custody officers,either due to lack of skills and understanding of the apparatus or due tonegligence which resulted in the detainee escaping.This type of research can be classified into empirical sociologicalresearch. With the research location located in Pekanbaru City, especially in thejurisdiction of the Pekanbaru City Resort Police, while the population and sampleare all parties related to the problem under study. This research uses data sourcesin the form of primary data and secondary data, and data collection techniquesare carried out by interview.From the research results of the problem there are 3 main things that canbe concluded. First, the process of resolving sanctions of detention guard officersagainst escaped prisoners is subject to disciplinary sanctions and disciplinarysanctions due to negligence in not carrying out their duties properly resulting inprisoners escaping. Second, the obstacles in the process of resolving the sanctionsof detention guards against escaped prisoners according to the Pekanbaru CityResort Police have no obstacles, because in the implementation process it iscarried out in accordance with statutory procedures, while according toAdvocates OBH PAHAM Riau must have obstacles in the process, because in theprocess of resolving sanctions the lack of assertiveness of the leadership towardstheir subordinates, should make the detention guard officer involved in findingdetainees, then sanctions will be given to the detention guard officer. Third, theefforts made in overcoming the obstacles are by means of leaders alwaysreminding their subordinates of their duties and responsibilities as prisoner guardofficers in order to anticipate events like this not happening again in thePekanbaru City Resort Police.Keywords : Process - Guard Officer – Prisoner.